A Network Perspective for Community Assembly - Ponisio, Lauren C.; Valdovinos, Fernanda S.; Allhoff, Korinna T.; Gaiarsa, Marília P.; Barner, Allison; Guimarães, Paulo R.; Hembry, David H.; Morrison, Beth; Gillespie, Rosemary (Frontiers in Ecology and Evolution, 2019)
Species interactions are responsible for many key mechanisms that govern the dynamics of ecological communities. Variation in the way interactions are organized among species results in different network structures, which translates into a community's ability to resist collapse and change. To better understand the factors involved in dictating ongoing dynamics in a community at a given time, we must unravel how interactions affect the assembly process. Here, we build a novel, integrative conceptual model for understanding how ecological communities assemble that combines ecological networks and island biogeography theory, as well as the principles of niche theory. Through our conceptual model, we show how the rate of species turnover and gene flow within communities will influence the structure of ecological networks. We conduct a preliminary test of our predictions using plant-herbivore networks from differently-aged sites in the Hawaiian archipelago. Our approach will allow future modeling and empirical studies to develop a better understanding of the role of the assembly process in shaping patterns of biodiversity.